The insider's guide to mental health resources online - Grohol, John M. (The clinician's toolbox, a Guilford series, 1997)
Part I: Basic map and tools for finding mental health information online Why and how to look online Knowing where to look online Part II: Getting answers to your professional questions Finding disorders, subspecialties, clinical and treatment information online Locating employment opportunities through the Web Online education and continuing education resources Networking with other professionals online Researching online: References and databases Professional associations, issues, and ethics online Book publishers, bookstores, and journals online Finding and downloading software online Online therapy and behavior Part III: Patient education resources General consumer-oriented resources on the Web Consumer mailing list discussion and support groups Consumer newsgroup discussion and support groups Part IV: Appendices Appendix A: Glossary of terms Appendix B: Further reading Appendix C: How to get online Appendix D: Creating your own Web resource